Mechanical and chemical properties of composite materials made of dredged sediments in a fly-ash based geopolymer. (15th April 2017) - Lirer, S.; Liguori, B.; Capasso, I.; Flora, A.; Caputo, D.
Abstract: Dredging activity in harbours and channels produces huge quantities of sediments, generally considered as waste soil (WS) to be disposed: the management of such sediments is a great environmental problem for many countries worldwide. Among the recycling possibilities, the use of dredged sediments for the manufacture of geopolymer-based materials seems to be an interesting alternative to disposal, due to their low cost and easy availability. In order to analyse the possibility to use these geopolymer materials as building materials – for instance as precast construction elements in maritime projects - a multi-disciplinary research activity has been developed at the Federico II University of Napoli (Italy). Some experimental tests have been carried out on different geopolymeric specimens made by mixing sediments from Napoli 'harbour and industrial fly ashes produced by a power plant in the South of Italy. A siliceous sand was used for comparison as an inert reference material. Chemical, morphological and mechanical properties of different specimens have been studied by X-ray diffraction, Scanning Electron Microscopy (SEM), Fourier transformed infrared spectroscopy (FTIR) and finally unconfined compression tests. The experimental results highlight that the use of dredged sediments in combination with fly ash can lead to geopolymeric matrices with interesting mechanical performances. Some differences in the microstructure of the geocomposite built with the siliceous sand or the dredged materials were found. In terms of environmental impacts, on the basis of standard leaching tests and according to Italian thresholds, the adopted dredged mixtures satisfy the prescribed limit for inert or non hazardous waste. Graphical abstract: Highlights: The management of dredged sediments is an environmental problem for many countries. Geopolymers were prepared by mixing harbour's sediments and industrial fly ashes. The fly ash was employed to produce a geopolymer-based building material. The stress-strain behaviour is typical of an artificially structured soil. Leaching compliance test classify the geocomposite as a non-dangerous material.